Venous thromboembolism: incidence, recurrence and mortality - Arshad, Nadia (UiT The Arctic University of Norway, 2018)
Paper I is as a published version not available in Munin. Paper IV is not available in Munin. Paper I: Arshad, N., Isaksen, T., Hansen, J.B. & Brækkan, S.K. (2017). Time trends in incidence rates of venous thromboembolism in a large cohort recruited from the general population. The submitted manuscript version of this paper is available in Munin: http://hdl.handle.net/10037/13015.The published version of this paper is available in European Journal of Epidemiology, 32(4), 299-305. Paper IV: Arshad, N,, Lijfering, W.M., Cannegieter, S.C., Hansen, J.B., Rosendaal, F. & Brækkan, S.K. Myocardial infarction is a risk factor for venous thromboembolism (VTE) recurrence in women with a first VTE. (Manuscript). Deep vein thrombosis (DVT) and pulmonary embolism (PE), collectively referred to as venous thromboembolism (VTE), is associated with substantial morbidity and mortality. To plan and evaluate prevention and treatment strategies for VTE, understanding into the epidemiology and current magnitude of VTE is needed. The aims of this thesis were (i) to assess time-trends in the incidence of VTE in the period 1996-2012, (ii) to assess the incidence of recurrence and mortality after a first VTE, and to investigate association between (iii) hospital-related, and (iv) myocardial infarction (MI)-related first VTE and risk of VTE recurrence. All four papers in this thesis utilize the Tromsø Study, a large population-based cohort with repeated health surveys (1-7). In paper I, we followed 26 855 participants from the inclusion in Tromsø 4 (1994-95) throughout 2012, and assessed the biennial incidence rates of VTE. In Papers II-IV, patients with a first VTE in the period 1994-2012 derived from Tromsø 4 (Paper II) or Tromsø 1-6 (Papers III and IV) were followed from their first VTE until the date of recurrence, death or emigration, or the end of the study period, whichever came first. Paper IV additionally included data from the Multiple Environmental and Genetic Assessment of Risk Factors for venous thrombosis (MEGA) ...